2018
DOI: 10.1155/2018/9701619
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Distribution Width at First Day of Hospital Admission in Patients with Hemorrhagic Fever with Renal Syndrome Caused by Hantaan Virus May Predict Disease Severity and Critical Patients’ Survival

Abstract: Thrombocytopenia is one of the main characteristics of hemorrhagic fever with renal syndrome (HFRS). This study aimed to evaluate the associations of platelet distribution width (PDW) with the disease severity and critical patients' survival of HFRS. The demographics, clinical data, and white blood cell and platelet parameters including PDW in 260 patients hospitalized for HFRS were analyzed. The results showed that PDW on the first day (PDW1) was positively associated with the disease severity (p = 0.005). Mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 32 publications
(46 reference statements)
0
9
0
1
Order By: Relevance
“…A prognostic role for thrombocytopenia in the HFRS has been suggested. In patients with HFRS caused by Hantaan orthohantavirus infection, the platelet distribution width at admission was reported as a mortality risk factor [24], while an independent association between nadir platelet count and development of severe acute kidney injury has also been described in these patients [25]. Interestingly, thrombocytopenia has been associated with capillary leakage and severity of inflammation in Puumala orthohantavirus infection [26].…”
Section: Discussionmentioning
confidence: 99%
“…A prognostic role for thrombocytopenia in the HFRS has been suggested. In patients with HFRS caused by Hantaan orthohantavirus infection, the platelet distribution width at admission was reported as a mortality risk factor [24], while an independent association between nadir platelet count and development of severe acute kidney injury has also been described in these patients [25]. Interestingly, thrombocytopenia has been associated with capillary leakage and severity of inflammation in Puumala orthohantavirus infection [26].…”
Section: Discussionmentioning
confidence: 99%
“…This mechanism leads to the aggravation of the patient's condition [18] . Other studies have shown that WBC, PLT, platelet distribution width (PDW) and PCT can be used as valuable parameters for the severity of HFRS patients, especially the change of PDW on the rst day of hospitalization is related to the survival rate of severe HFRS patients and can be used as potential predictors [19] . In this study, the increase of WBC in patients with severe HFRS was signi cantly higher than that in mild patients, whereas a study showed that compared with leukocytosis, thrombocytopenia may better predict the prognosis of severe acute kidney injury (AKI) in patients with acute HTNV infection [20] .…”
Section: Discussionmentioning
confidence: 99%
“…This mechanism leads to the aggravation of the patient's condition [18] . Other studies have shown that WBC, PLT, platelet distribution width (PDW) and PCT can be used as valuable parameters for the severity of HFRS patients, especially the change of PDW on the rst day of hospitalization is related to the survival rate of severe HFRS patients and can be used as potential predictors [19] . In this study, the increase of WBC in patients with severe HFRS was signi cantly higher than that in mild patients, whereas a study showed that compared with leukocytosis, thrombocytopenia may better predict the prognosis of severe acute kidney injury (AKI) in patients with acute HTNV infection [20] .…”
Section: Discussionmentioning
confidence: 99%